HYDROELECTRIC POWER FOR HYDROGEN GENERATION IN ECUADOR - Contreras Vásquez, Luis (2023)
This work focuses on explaining the viability of the implementation of hydrogen technology as an alternative to the use of fossil fuels, using hydroelectric renewable energy sources, for that purpose, an evaluation of the growing energy demand and the current state of environmental pollution is carried out. Various alternatives are proposed for the production of hydrogen, and electrolysis of water stands out considering the efficiency and economic viability of the process. A comparative analysis of the technologies used in various countries to obtain hydrogen through hydroelectricity is also performed. Finally, the possibility of using hydrogen technology as a complement to increase the efficiency factor of hydroelectric plants in Ecuador is determined, thus contributing to a change towards a clean and renewable energy matrix that is economically sustainable.